Answer:
1. S(1) = 1; S(n) = S(n-1) +n^2
2. see attached
3. neither
Step-by-step explanation:
1. The first step shows 1 square, so the first part of the recursive definition is ...
S(1) = 1
Each successive step has n^2 squares added to the number in the previous step. So, that part of the recursive definition is ...
S(n) = S(n-1) +n^2
__
2. See the attachment for a graph.
__
3. The recursive relation for an arithmetic function is of the form ...
S(n) = S(n-1) +k . . . . . for k = some constant
The recursive relation for a geometric function is of the form ...
S(n) = k·S(n-1) . . . . . . for k = some constant
The above recursive relation is not in either of these forms, so it is neither geometric nor arithmetic.